PENGARUH EXAMPLE DAN NON-EXAMPLE TERHADAP KETERAMPILAN MENYIMAK DI SEKOLAH DASAR - Yusnadi Rahmad Hidayat; Kaswari Kaswari; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to analyze how much influence the use  example and non- example toward listening skill of fifth grade students Primary School 09 Pontianak Tenggara. This research used experimental methods Quasy type experiment. The population in this study were all fifth grade students of Elementary School 09 Pontianak Tenggara. Samples were students accounted for 26 students. Based on the analysis of data obtained by the average post-test control class average of 51,62 and post-test experimental classroom 71.31. The results of hypothesis testing using t-test for the obtained t = 7.108 % was obtained t_tabel of 2.779 which means t_hitung> t_tabel (7.108>2.779), the Ha received. Thus, it can be concluded that there are influence the use example and non- example toward listening skill of fifth grade students Elementary School 09 Pontianak Tenggara. Keywords :The Impact, Example and Non- Example, Listening Skill.